(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2015)
The paper presents the methodology and results of geoecological zoning of Yerevan and surrounding areas. Unmodified, modified and highly modified areas have been outlined by the method of mathematical weighing.